Presence of women on boards in industrial firms: evidence from GCC countries financial markets - Hamdan, Reem (2021)
This study aims to investigate the phenomenon of women's presence on the boards of industrial public companies in the Gulf Cooperation Council (GCC) countries. The first question deals with the relationship between board characteristics, governance variables and women on boards. The second question weighs the impact of the company-specific characteristics on the presence of women on boards. Our study focuses on 125 public companies listed on the Gulf financial markets and operating in the industrial sector for the year 2019. Results indicate that both corporate governance and company-specific variables can explain the presence of women on boards. First, our results give evidence that the appointment of women directors is positively related to institutional ownership and board independence, and negatively related to board size. Second, the appointment of women directors is positively related to firm performance, but negatively related to firm size and leverage. Hence, taken altogether, the evidence suggests that the appointment of women on board is driven by the business case. The study stresses on the need to improve governance variables and to activate policies supporting women’s roles in GCC economies as their integration on the labor market and their participation in senior management is a means to achieve justice and fairness.